Comparison of sulphonamides decomposition efficiency in ozonation and enzymatic oxidation processes - Natalia Lemańska; Ewa Felis; Marzena Poraj-Kobielska; Zuzanna Gajda-Meissner; Martin Hofrichter (Archives of Environmental Protection, 2021)
Sulphonamides (SAs) are one of the most frequently detected anthropogenic micropollutants in the aquatic environment and their presence in it may pose a threat to living organisms. The aim of the study was to determine susceptibility of selected sulphonamides, i.e. sulfadiazine (SDZ) and sulfamethazine (SMZ), to degradation in the ozonation process and in enzymatic oxidation by unspecific peroxygenase extracted from Agrocybe aegerita mushroom ( AaeUPO). Moreover, the acute toxicity of the aqueous solution of the selected sulphonamides (SMZ and SDZ) before and after mentioned treatment processes were studied on the freshwater crustacean Daphnia magna. Initial concentrations were equal to 2×10-5 M for sulfadiazine and 1.8×10-5 M for sulfamethazine. The percentage of transformation for the O3 process was at the level 95% for both SDZ and SMZ (after 10 s of the process), whilst enzymatic oxidation of SDZ and SMZ by AaeUPO caused transformation efficiencies at the levels of 97% and 94% (after 1 minute of the process), respectively. The second order rate constants of selected sulfonamides with molecular ozone and fungal peroxidase were also determined in the research. EC50 (median effective concentration) values from toxicity test on D. magna were found in the range from 14.6% to 37.2%, depending on the type of the process. The conducted oxidation processes were efficient in degradation of selected sulphonamides. The toxicity of the mixtures before and after treatment was comparable and did not change significantly. The research have shown that biological processes are not always safer for living organisms compared to the chemical processes.